1256. New Acquisitions of ET-12 Burkholderia cenocepacia in Adults With Cystic Fibrosis: Role of Whole Genome Sequencing in Outbreak Investigation. (26th November 2018) - Blanchard, Ana C; Tadros, Manal; Tang, Lin; Muller, Matthew; Spilker, Theodore; Waters, Valerie; Lipuma, John; Tullis, Elizabeth
Abstract: Background: Transmission of Burkholderia cenocepacia ET-12 strain (ET-12Bc) can cause epidemics in the cystic fibrosis (CF) population. The Toronto Adult CF center currently follows 500 patients; 20% have infection with B. cepacia complex (BCC), including 48 patients infected with ET-12Bc. The center adheres to the 2013 infection prevention and control guidelines and patients are also segregated by clinics. Despite this, there have been 11 new acquisitions of ET-12Bc since 2008. The objective of this study was to describe the investigation of an ET-12Bc outbreak in CF patients, using whole-genome sequencing (WGS). Methods: Investigations included multilocus sequence typing (MLST) and WGS of 34 isolates (11 new ET-12Bc acquisitions, 18 isolates of known ET-12Bc patients (including all patients with hospital admissions that overlapped with new acquisitions), four isolates from CF patients in the USA and the J2315 reference strain). Each of the seven MLST alleles from ET12Bc strain J2315 was downloaded from PubMLST and used to "Blast" each of the 16 WGS databases. WGS was done using 150 bp paired-end runs on an Illumina HiSeq4000. Single nucleotide polymorphisms (SNPs) between the newly sequenced strains and J2315 were profiled. Results: Ten patients had a hospital admission within the 2 months preceding their first ET-12Bc positive sputum culture, except for one in whom ET-12Bc was detected 12 months following hospital admission. In all isolates, the seven alleles ( atpD, gltB, gyrB, recA, lepA, phaC and trpB ) matched 100% to sequence type 28 and clonal complex 31, and were identical to J2315. WGS SNP analysis confirmed that transmission occurred from known cases on the unit in 10/11 (90.9%) patients. To date, 8/11 patients with new acquisitions have died (median survival of 95 days). Conclusion: Our investigations found epidemiological evidence suggestive of ET-12Bc transmission on the CF unit, which was confirmed by MLST and WGS SNP analysis. Compared with MLST, WGS SNP analysis had better discriminatory power and was well correlated with the identified epidemiological links between patients. Recognition of ET-12Bc transmission with associated high mortality rates has led to a change in our hospital policy. ET-12Bc positive patients will no longer be cared for on the same unit as ET-12Bc negative patients with CF. Disclosures: All authors: No reported disclosures.